Reverse vaccinology as an approach for developing Histophilus somni vaccine candidates. Issue 6 (November 2015) - Madampage, Claudia Avis; Rawlyk, Neil; Crockford, Gordon; Wang, Yejun; White, Aaron P.; Brownlie, Robert; Van Donkersgoed, Joyce; Dorin, Craig; Potter, Andrew
Abstract: Histophilosis of cattle is caused by the Gram negative bacterial pathogen Histophilus somni ( H . somni ) which is also associated with the bovine respiratory disease (BRD) complex. Existing vaccines for H. somni include either killed cells or bacteria-free outer membrane proteins from the organism which have proven to be moderately successful. In this study, reverse vaccinology was used to predict potential H. somni vaccine candidates from genome sequences. In turn, these may protect animals against new strains circulating in the field. Whole genome sequencing of six recent clinical H. somni isolates was performed using an Illumina MiSeq and compared to six genomes from the 1980's. De novo assembly of crude whole genomes was completed using Geneious 6.1.7. Protein coding regions was predicted using Glimmer3. Scores from multiple web-based programs were utilized to evaluate the antigenicity of these predicted proteins which were finally ranked based on their surface exposure scores. A single new strain was selected for future vaccine development based on conservation of the protein candidates among all 12 isolates. A positive signal with convalescent serum for these antigens in western blots indicates in vivo recognition. In order to test the protective capacity of these antigens bovine animal trials are ongoing.